INTEGRATING SOCIO-SCIENTIFIC ISSUES (SSI) APPROACH BASED ON SDGS FOR GENERATION ALPHA IN ELEMENTARY SCHOOLS - Annas Solihin; Suryanti; Enny Susiyawati; Julianto; Endang Susantini; Ari Metalin Ika Puspita (Universitas Majalengka, 2025)
Socio-Scientific Issues (SSI)-based learning has become increasingly significant in addressing global challenges, particularly for Generation Alpha, who are growing up in the digital era. This study aims to analyze the effectiveness of the SSI-based learning approach within the context of the Sustainable Development Goals (SDGs) at the elementary school level. A qualitative research approach with a case study design was employed, involving observations, interviews, and document analysis of educators and students from several elementary schools. The findings indicate that implementing SSI-based learning contributes to enhancing students' understanding of global issues while simultaneously strengthening critical thinking, problem-solving, and collaboration skills. Educators play a central role in designing interactive and technology-based learning strategies to increase student engagement. However, challenges remain in implementing this approach, including teachers' readiness and limited learning resources. Therefore, integrating SSI-based learning within the SDG framework in elementary education can be an effective strategy for improving students' scientific literacy and social awareness. Further research is needed to develop training strategies for educators and expand the implementation of this method across various educational contexts. In conclusion, integrating the SSI approach based on SDGs into science education in elementary schools has great potential to enhance scientific literacy, social awareness, and 21st-century skills among students.